Nutrient cycling at cattle feedlots field & laboratory study - Vaillant, Grace C. (Kansas State University, 2007)
Soil chemical and physical properties beneath cattle feedlot pens are largely unstudied. This project was conducted to survey select soil chemical and physical properties of soil beneath active open air cattle feedlots. At four cattle feedlots in Kansas, the concentrations of NH4-N, organic-N, organic-C, Cl-, and P were high at the surface and rapidly decreased within 1.00 m. At three of the four feedlots, NO3-N was generally below background concentration (4.1 mg kg-1) while one feedlot had a >75 mg kg-1 increase in the top 1.00 m. Based on feeding data, only a small percent (7.9 to 1.2) of the total N deposited on the surface was found in the top 1.00 m below the pen surface for a range of 25 to 60 years of operation. While in use, these feedlots do not appear to have a high potential for groundwater pollution from NO3-N leaching. However, if they were to become inactive they may pose a severe threat to groundwater quality from organic-N mineralization and NH4-N nitrification. If feedlots were closed and the land could be largely remediated by removing a layer of soil, these feedlots would have an average 48% profile N removed in a 0.25 m thick layer. A chamber, a modified vacuum desiccator, was tested for the investigation of NH3 volatilization from soil in the laboratory. Ammonia volatilization at the soil surface is dependent on air flow, soil and air temperatures, soil water content, pH, the concentrations of NH3 and NH4+ in the air and soil solution, and factors affecting soil temperature including humidity. This chamber was built to control and/or quantify as many of these variables as possible. A technique for quantifying and predicting NH3 volatilization is important because AFOs are one of the largest contributors of NH3 to the atmosphere, which can cause acid precipitation and particulate matter deposition downwind from the operation. The chambers created allowed for repeated measurements with little error and appear to be a feasible, inexpensive apparatus to investigate NH3 volatilization mechanisms. Using synthetic urine as an N source, NH3 volatilization was affected by initial soil moisture content and soil texture and may be affected by initial soil pH. This chamber has promise to provide excellent data to assist the efforts being made to understand and model NH3 volatilization from feedlot pens.
Keywords: Cattle feedlots; Nutrient profiles below pens; Ammonia volatilization; Dynamic chamber; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)